Pengaruh Kecerdasan Emosional terhadap Kinerja Pegawai yang Dimediasi oleh Profesionalisme - Dian Amelia Putri; Zulfina Adriani; Fitri Chairunnisa (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to describe and determine the influence of Emotional Intelligence on Employee Performance Mediated by Professionalism at the Jambi City Population and Civil Registration Office. The analytical method of analysis used is quantitative analysis. The population and research sample were all employees at the Jambi City Population and Civil Registration Office, totaling 88 respondents. Data collection was carried out by distributing questionnaires using a Likert scale. The statistical analysis used is the Structural Equation Modeling (SEM) technique with Partial Least Square (PLS) as an analytical tool, using the SmartPLS 4 program. The results of statistical analysis show that emotional intelligence has a positive and significant effect on employee performance, emotional intelligence has a positive and significant effect on professionalism, professionalism has a positive and significant effect on employee performance, and emotional intelligence through professionalism as a mediating variable has a positive and significant effect on employee performance. So it can be concluded that professionalism functions as a link between emotional intelligence and employee performance. If employees have good emotional intelligence, then employees can manage their potential optimally so that they will produce good performance so that the stated organizational goals will be achieved.